MEN’S HEALTH AND THE INFLUENCE OF TESTOSTERONE AND ITS ANALOGS IN THE IMMUNE RESPONSE: A REVIEW - Henrique Oliveira De Souza, Pedro; Cristina Zimmermann Franco, Danielle (Health and Society, 2023)
Introduction: Testosterone and its analogues are described in the literature as immunomodulators. The use of androgen anabolic steroids transcends age, which requires research that points to the specific care needed for these patients, usually male. In addition, the use of this hormone can have deleterious consequences for immunity, with the risk of triggering greater problems. Thanks to ingrained sexism in society, men tend to seek health services less. Objective: To report the interactions of testosterone with the male immune system, addressing its lower search for health services, and from that, to suggest a physiological cause that complements the sociological one. Methods: Bibliographic review of works from the English and Portuguese medical literature, published from 2004 to 2022 and found on Google Scholar, PubMed and Scielo. Literature Review: Due to the high titers of the hormone, men tend to generate a weaker immune response to diseases, compared to women. Testosterone and its analogues are also described as inhibitors of antioxidant activity, helpers in the gain of secondary sexual characteristics, and recovery agents in physical exercises. The immunosuppression generated by this hormone is one of the possible undesirable effects of its use. Because of this, elderly men on hormone replacement are susceptible to the same immunosuppression, which requires greater monitoring. Final Considerations: Testosterone usually has immunosuppressive activity, masking symptoms. Such severity increases when talking about the male public, since there is already a tendency to abstain from health services, thanks to the sexist factor present in society.